Pregnancy Massage Reducing Back Pain For Pregnant Women - Nurul Haflah; Yulia Safitri (Akupun Tour Publisher, 2022)
Changes in the musculoskeletal system often cause pregnant women to feel pain in the lower back area. Back pain is one of the discomforts that often occurs in third trimester pregnant women, which is an adaptation process in the body of pregnant women. About 80% of women experience back pain at some point during pregnancy. This occurs 70% due to changes in the spinal muscles, while 30% may be due to problems with previous spinal conditions. The purpose of the study was to determine the effect of pregnancy massage on back pain in pregnant women and to find out the difference in pain between the treatment and control groups. The research method used a quasi-experimental design with a non-randomized pretest and posttest with a control group design. Sampling was carried out by non-random sampling with purposive sampling technique. Data analysis used the Wilcoxon and Mann-Whitney test. The results showed that there was a significant effect of giving pregnancy massage on the back on back pain in third trimester pregnant and there was a difference in pain in third trimester pregnant women in the treatment and control groups as evidenced.